Variations in δ¹³C and δ¹⁵N of pantropical spotted dolphins (Stenella attenuata) explained by intrinsic and extrinsic factors - Cañete, Ana Janelle H. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The pantropical spotted dolphin (Stenella attenuata) occupies pelagic habitats and is migratory. Observing this species is difficult and little is known about their ecology. Stable isotope analysis allows us to make inferences on cetacean ecology even without constant observation. In this study, I analyzed data collected by Evacitas (2017) on the dentinal δ¹³C and δ¹⁵N of S. attenuata. I aimed to determine how isotopic signatures of S. attenuata change due to life history and what factors contribute to these changes. I compared the dentinal δ¹³C and δ¹⁵N belonging to groups of different variables (sex, life history, stranding area, and year of isotope accumulation). A generalized additive model was fitted to determine the influence of the aforementioned variables. I found that variations in δ¹⁵N occurred due to age, life history, and sex. On the other hand, δ¹³C values were affected by age, life history, sex, and spatio-temporal factors. The prenatal and one-year calf layers are enriched in 15N while the one-year and two-year calf layers are depleted in δ¹³C. The δ¹³C values in male calves were significantly lower than that in female adults while the δ¹⁵N of male juveniles was significantly higher than that of female juveniles. These results reflect dietary differences and have implications on breeding strategy and parental investment. Male and female adults have similar isotopic signatures, confirming observations that S. attenuata aggregate in communities of mixed ages and sexes. A linear decrease in the values of δ¹³C over time is suggestive of the Suess effect, which is caused by anthropogenic activity. Spatial variation in δ¹³C indicates differences in primary productivity but cannot be correlated with currently existing data. Overall, the results of this study provide more insight into the ecology of the pantropical spotted dolphins.